KONTRIBUSI MAJELIS ULAMA INDONESIA DALAM PROSES PEMBENTUKAN DAN IMPLEMENTASI UNDANG-UNDANG NOMOR 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH - Suhadak, Faridatus; Priadi, Eko (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
In response to the rapid development of Islamic economic, especially in Islamic banking, hence made Act number 21 Year 2008 on Islamic Banking. Thus, the Act No. 21 year 2008 is a legal framework for the implementation of Islamic Banking in Indonesia. The enactment of Law No. 21 year 2008 is certainly can not be separated from the role of the Indonesian Ulama Council who have contributed substantially in supporting and patronizing Islamic Banking. This study is a normative research with qualitative approach that resulted the role of Indonesian Ulama Council in the formulation Act No. 21 year 2008. First, the involvement of National Shariah Council (DSN - MUI) in the assessment process, deepening and refinement of the substance of the formulation of Islamic Banking. Second, the recommendation and statement issued by the MUI related to the Act Number 21 Year 2008 on Islamic Banking. The MUIâ€™s role in the implementation of Act No. 21 year 2008 on Islamic Banking consists of two functions, i.e. regulatory functions are realized in the form of DSN - MUI fatwas related to Islamic Banking and control functions are realized in the form of DSN - MUI authority to recommend DPS in Islamic banks, give warning to non-compliant Islamic banks and propose to the authority to take action if the warning is ignored. This study recommends the need for effective coordination between the DSN - MUI with other stakeholders regarding fatwas/regulations produced to be implemented well. Â